2011
DOI: 10.1002/hpm.1105
|View full text |Cite
|
Sign up to set email alerts
|

Weaknesses and Challenges of Primary Healthcare System in Iran: A Review

Abstract: While the primary healthcare (PHC) services in Iran were appropriate to the needs of the population in the late 1970s and 1980s, the changing burden of disease and shifting demand patterns have rendered the existing PHC system no longer suitable for meeting current and emergent needs. This has serious implications for the PHC system in Iran, which has clearly succeeded in addressing high levels of communicable diseases, maternal deaths and infant mortality, but appears less well prepared to address the emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 7 publications
4
70
0
Order By: Relevance
“…Promoting health is not only a responsibility but also a right and as mentioned by the Iranian constitution, the government must provide health care to population on an equitable basis (1). Iran has signed the Alma-Ata Declaration in 1978, aiming health for all by the year 2000 using the primary health care (PHC) strategy (2). Moving in this direction, policymakers in Iran decided to enact and enforce the laws to reach the goal (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promoting health is not only a responsibility but also a right and as mentioned by the Iranian constitution, the government must provide health care to population on an equitable basis (1). Iran has signed the Alma-Ata Declaration in 1978, aiming health for all by the year 2000 using the primary health care (PHC) strategy (2). Moving in this direction, policymakers in Iran decided to enact and enforce the laws to reach the goal (3).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reforms, organizational structure of PHC system has not changed over the last thirty years (2). Organizational structure reform is required to have appropriate performance regarding new goals and strategies (9).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for the purpose of implementing the second phase of Iranian Targeted Subsidy Plan, "Health Reform Program" was designed, and a large budget was allocated to the health sector. The project consisted of seven programs including special packages to reduce the costs of patients in public hospitals, but it cannot yet be judged due to the unavailability of data about it (33,34). According to the new population policy, and in order to increase the country's population, the annual population growth rate and total fertility rate will probably increase.…”
Section: Iran J Health Sci 2017; 5(2): 39mentioning
confidence: 99%
“…However, most studies conducted on the Iranian primary health care system showed that, despite having numerous achievements, it had notable weaknesses. Nekoei Moghadam et al referred to the weakness of the system in urban areas and the existence of several centers with different providers (8). In its report on the Iranian health system in 2007, the World Bank highlighted many of the Iranian health system achievements after the expansion of health networks, and then mentioned some of the existing problems, including the multiplicity of service delivery systems and fragmentation of the health system, especially in cities (9).…”
Section: Introductionmentioning
confidence: 99%